The Matthean Beatitudes : Its Literary Function and Theological Message - Pranoto, Irwan (Trinity Theological College, 2010)
This research discusses the literary form and structure of the Matthean Beatitudes in order to delineate its particular literary function and theological message. At the outset, it is submitted that the first discourse of Matthew’s Gospel has a didactic purpose. This argument is supported by the literary characteristics and structure of Matthew and the structure and content of the Sermon on the Mount itself. Next, it examines the prominent literary characteristics of the passage in order to determine its particular literary function. The discussions include the following: first, the poetical features of the passage, such as inclusion, repetitions, parallelism, chiastic pattern, word counts and selective usage of particular words, which function as delimitation signs and highlight the themes and structure of the Beattitudes; second, the formula of blessedness (macarisms) which functions to show that the Matthean Beatitudes have a common element with the Jewish wisdom and apocalyptic literature; and finally, the significance of the passage as the opening unit of Sermon on the Mount appropriately linking the sermon and its immediate context, also serving as the introduction for the literary structure of the sermon. After that, three theological themes are presented and discussed. These include the idea of absolute dependency on God’s grace in his Kingdom, the attitude toward the righteousness of the kingdom and finally the message of hope from the promises of the kingdom. By doing this foundational study for a proper understanding of the Matthean Beatitudes, a deeper appreciation for the passage is achieved and further studies for establishing certain tenets for Christian spiritual formation are proposed.
Keywords: Bible. Matthew -- Criticism, interpretation, etc.; Beatitudes -- Criticism, interpretation, etc.